Study on Marketing of Jowar (Sorghum) in Bareilly District of Uttar Pradesh - Kumar, Shivam; Kumar, Dr. Sanjay (International Journal of Environment, Agriculture and Biotechnology, 2024)
This research paper examines the marketing channels for Jowar (Sorghum) in Bareilly District, Uttar Pradesh, focusing on the cost, margin, efficiency, and price spread associated with each channel. The study identifies three primary marketing pathways: direct producer-to-consumer sales (Channel I), sales through village merchants or retailers (Channel II), and sales involving commission agents and wholesalers (Channel III). The research utilizes a systematic multi-stage stratified random sampling technique, collecting primary data through personal interviews and secondary data from relevant sources. The results reveal that Channel I, the direct marketing route, is the most efficient with the lowest marketing costs and a high efficiency of 48.81. Channels II and III, incorporating intermediaries, exhibit significantly lower efficiencies (5.87 and 5.15 respectively) and higher price spreads, indicating greater economic burdens for producers and consumers. These findings highlight the detrimental impact of intermediaries on market dynamics. The study advocates for reducing intermediary involvement to enhance marketing efficiency, improve producer profitability, and ensure fair pricing for consumers. This strategy promises to empower local farmers and promote sustainable agricultural practices.